Temporal trends in incidence of heart failure in relation to age and gender in western Sweden 2008–2017. (25th November 2020) - Wideqvist, M; Rosengren, A; Schaufelberger, M; Pivodic, A; Fu, M
Abstract: Background: During the last decades we have witnessed gradually improved cardiovascular primary and secondary prevention, while life expectancy is increasing, with a growing population of elderly people. Heart failure is a disease of the elderly and end stage of other cardiac diseases. Accordingly, trends in incidence of heart failure are dynamic and may differ by age and gender Purpose: To investigate overall trends in incidence for HF over the last decades in Western Sweden. Additionally we wanted to study incidence in relation to age and gender. Method: The VEGA database is an administrative database of all patients managed in hospital care (through direct linkage to the Swedish nationwide patient registry) and/or in primary care facilities (private and public) living in Western Sweden. All patients with a main or contributory diagnosis of HF (I50) >18 years of age between 2008 and 2017 were included in our cohort. HF incidence was calculated based on the entire population of Vastra Gotaland (a region of Western Sweden). Results: The adult population in Western Sweden increased by 8% from 2008 (n=1, 234, 609) to 2017 (n=1, 338, 906), with 69% <60 years of age and 50% female, both constant over time. In total, 62, 229 incident cases of HF were identified during 2008–2017. In 2008 we identified 6464 cases with a mean age of 78.7 (11.5) and 49.8% (n=3222) male patients, while in 2017 5, 727 cases were identified with a mean age of 78.3 (11.8) and 52.5% (n=3006) male cases. The yearly incidence rate of HF remained constant over the 10-year period but with large variations by age and gender. A constantly higher incidence of HF was seen for men compared to women in all age categories. Although overall incidence remained constant in the last decade, we did observe decreasing incidence among those >80 years of age with incidence rates dropping from 4.4% to 3.0% between 2008–2017 (80–90 years) and from 7.8 to 5.5% in the same period (>90 years of age). A similar pattern was seen in both men and women in these age groups with incidence decreasing over the last ten years. Conclusion: The overall incidence of HF remained unchanged over the last decade. However a declining trend in incidence was observed in the oldest part of the population, who, however, constitutes only approximately 5% of the population. Our findings emphasize the need for implementation of effective preventive strategies for HF. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): The Swedish agreement between the government and the county councils concerning economic support for providing an infrastructure for research and education of doctors (ALF), and the Regional Development Fund, Västra Götaland County, Sweden (FOU-VGR)